HUBUNGAN STIGMA DAN EFIKASI DIRI DENGAN KEPATUHAN PENGOBATAN OBAT ANTI TUBERKULOSIS (OAT) PASIEN TUBERKULOSIS: LITERATUR REVIEW - Suratmini, Dwi; Berliana Togatorop, Lina (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
Tuberculosis (pulmonary TB) is an infectious disease that causes death at world level which is influenced by patient non-adherence in undergoing treatment. The stigma given by the environment to tuberculosis sufferers creates self-stigma and self-efficacy in undergoing treatment. This study aims to explain the relationship between self-stigma and self-efficacy on patient adherence in taking anti-tuberculosis drug treatment. The research method used was a literature review based on PICOS through searching the article database from Google Scholar, PubMed, Scopus, and ScienceDirect from 2018–2023. The search results obtained 10,602 articles and 12 articles that were relevant for analysis. The inclusion criteria of the search were articles in Indonesian and English, published in the last 5 years, relevant to the stigma and self-efficacy of tuberculosis patients. Self-stigma and self-efficacy of tuberculosis patients are related to adherence to taking anti-tuberculosis drugs (OAT) which are influenced by the level of knowledge and support that tuberculosis patients get. Intervention to reduce self-stigma and increase self-efficacy can be given to tuberculosis sufferers to optimize adherence in undergoing treatment.